Regional Peer Effects of Corporate Tax Avoidance - Gao, Ya; Cai, Chang; Cai, Yiwei (Frontiers in Psychology, 2021)
This study empirically demonstrates significant regional peer effects due to tax avoidance. We used peer companies’ idiosyncratic stock returns as an instrumental variable to address potential endogeneity problems. The heterogeneity analysis indicates that for companies with a stronger intensity of regional tax collection and management, a higher degree of informatization, and companies with a low management shareholding ratio, the regional peer effects of enterprise tax avoidance are more significant. Finally, we determined that the managers’ information learning, reputation consideration, and information communication are key mechanisms propagating peer effects. The conclusions of this paper enrich and expand the peer effect theory of corporate tax avoidance, thereby providing a theoretical basis and empirical evidence for tax authorities in supervising corporate tax avoidance.